(Im)Politeness in the Khutbahs of Yoruba imams : a socio-pragmatic analysis - Kareem, Sharafudeen (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study investigated the linguistic (im)politeness behaviour of Yorùbá Imams in their English and Yorùbá khutbahs. Five Imams were purposively selected for the study from four Yorùbá states in Nigeria, resulting in a dataset consisting of 19 tape-recorded natural Jumu'ah khutbahs. They range between thirty minutes and an hour in length. The data is 115,549 words totally. Five khutbahs were delivered in English and three in Yorùbá, while the remaining eleven combined both languages. The politeness model of Brown and Levinson (1987) integrated with a discursive approach, Culpeper's impoliteness theory (1996, 2011a, 2016), was employed for a qualitative analysis of the data. It was found that the bald-on-record superstrategy mitigated with negative politeness strategies was the most frequently used option by the Imams followed by the unmitigated bald-on-record strategy. Also, the results revealed that positive and negative politeness devices were combined with some of the strategies to soften the Face-Threatening Acts (FTAs), and multiple strategies were often used to achieve the same effect. Furthermore, a number of positive politeness mechanisms were used outside FTA environments. In such situations, they were used to establish common ground with the co-participants, and to attend to their face wants and needs thereby enhancing their faces. Moreover, the study discovered that the Imams did not use nor preach anything that amounted to impoliteness which could cause violence or breed terrorism. In addition, the findings showed consistency between the Imams in terms of their (im)politeness behaviour in both languages. It also revealed that the Imams transferred some aspects of Yorùbá politeness culture to their use of English. However, a comparison between the two sets of data indicated that the Yorùbá khutbahs employed a higher number of politeness strategies than those found in the English ones. In conclusion, the study suggested that institutions and departments of Islamic education should, as a matter of necessity, teach (im)politeness to their students, who are potential preachers; and state ministries of religious affairs should have periodic programmes to teach Imams the art of khutbah delivery so that they can avoid impolite linguistic behaviour that could cause violence and/or train young ones in acts of terrorism, which has become a menace to the world today.